Application of Mesenchymal Stem Cell for Degenerative Disc Disease - Deby Susanti Pada Vinski; Carles Siagian; Andi Kurniawan Nugroho; Marhaen Hardjo; Natasha Cinta Vinski (Journal of World Science, 2024)
During a person's life, the spine will experience continuous changes in response to physiological axial loads. Increasing age is also a cause of pathological degenerative changes. Degenerative disease of the spine is a condition that many people complain about and requires appropriate and effective treatment. Degenerative disc disease is the most common cause of low back pain and disability worldwide, involving people of all ages and socioeconomic statuses. This study aims to explain and analyze the effectiveness of Mesenchymal Stem Cell therapy in treating Degenerative Disc Disease. The research method used is a case study where  Mesenchymal Stem Cell therapy offers the potential to modify the natural recovery of Degenerative Disc Disease using stem cell-based technology. Case studies were carried out at the Vinski Regenerative Center clinic, on several patients. And the results are that stem cells have the potential to be an ideal non-surgical treatment for low back pain and degenerative disc disease, because of their ability to differentiate into various connective tissue cells and their ability to restore damaged tissue and the results of case studies have proven to tend to improve the condition. However, long-term clinical studies are still needed, specifically focusing on the safety and efficacy of stem cell therapy in degenerative disc disease.